Ecologization of the tradition of tying zurams, khadaks and khii-morins at places of worship in the Republic of Buryatia - Dorzhigushaeva, Oyuna V.; Kiplyuks, Aryana V. (The New Research of Tuva, 2023)
The study examines the phenomenon of the transformation of the Buddhist tradition of offering ritual ribbons and flags (zurams, hadaks, and hiy-morins) in the Republic of Buryatia under the influence of environmental demands. Empirical data were gathered during field expeditions to sacred sites and Buddhist monasteries in the Republic of Buryatia from 2020 to 2023. The research involved the collection of photographic evidence, interviews with Buddhist lamas, temple personnel, and laypersons, as well as an analysis of organization websites and materials from the regional press. Initially, the tradition itself, associated with offerings, did not pose any negative environmental impact since the fabrics used were natural and biodegradable, and the method of tying employed by believers was not tight. However, contemporary practices have undergone significant changes, including the use of artificial fabrics for ribbons. This tradition became widespread and began to harm trees due to the substantial number of ribbons tied to them. Additionally, a consequence of the COVID-19 pandemic was the emergence of a new trend: tourists started tying medical items, such as masks and tissues, at sacred sites. Since 2014, the Buddhist Traditional Sangha of Russia has urged believers to address this issue, leading to lamas and activists performing cleansing rituals at worship sites. This initiative has facilitated the promotion of environmental awareness among the population. Thus, the authors highlight a rational approach by religious and social movements in the republic to rectify the situation.